Neglected and underutilized species: what they are and why the world needs them more than ever - Padulosi, Stefano; Meldrum, Gennifer; Israel Oliver King. E.D.; Hunter, Danny (Routledge, 2021)
The chapter provides an overall introduction to neglected and underutilized species (NUS) in the light of latest findings, trends and opportunities. There is a mounting interest in these species, driven in particularly by the need to make food and production systems more resilient to climate change. This chapter offers some reflections on what we mean when we refer to these local resources, wild or under cultivation, and why the international community should be paying more attention to enhancing their use.